Decacarbonyltetra-?-hydrido-bis(tricyclohexylphosphine)-tetrahedro-tetraruthenium - Lozano Diz, Enrique; Therrien, Bruno; Süss-Fink, Georg (My University, 2003)
The title cluster, [Ru4H4(C18H33P)2(CO)10], which contains two tricyclohexylphosphine ligands, was synthesized and characterized both spectroscopically and crystallog. The mol. structure is very similar to that of the known PPh3 deriv. [H4Ru4(CO)10(PPh3)2]. Crystals are monoclinic, space group P21/c, with a 12.461(5), b 23.934(5), c 18.541(5) Å, ? 96.545(5)°; Z = 4, dc = 1.510; R = 0.027, Rw(F2) = 0.045 for 10,053 reflections. [on SciFinder(R)]
Keywords: ruthenium cluster carbonyl hydro tricyclohexylphosphine prepn crystal structure; mol structure ruthenium cluster carbonyl hydro tricyclohexylphosphine